Los ingenieros y “la nacionalidad en construcción” - López Soria, José Ignacio (2022)
This article alludes to the tradition among peruvian intellectuals at the end of the 19th century and the beginning of the 20th that refer to Peru as a “nationality in formation”, and focuses on the use that engineers make of this category, in addition to studying the relationship established between nationality in formation and the general idea of ​​progress.